Work-life imbalance, burning out, feeling down, I will quit, but quietly – the case of hospitality employees - Prentice, Catherine (2024)
Given the long and irregular working hours and low wages in the hospitality sector, employees often experience poor well-being and suffer from burnout. Instead of leaving their jobs, these employees engage in quiet quitting, which negatively impacts organizations. This study investigates the relationships between role conflicts, employee well-being, burnout, and quiet quitting among hospitality employees. The study was undertaken at hotels with different star ratings in Portugal. Data were collected from both frontline and backstage employees from different departments at the survey hotels, Structural equation modeling with Mplus was performed to analyze the data. The results indicate that role conflicts affect well-being and increase burnout, leading to quiet quitting. Furthermore, well-being and burnout mediate the relationship between role conflicts and quiet quitting, suggesting indirect effects of role conflicts. Gender and age also significantly influence these relationships. This study contributes to positive psychology and burnout research by evaluating an integrative model of role conflicts, well-being, and job-related outcomes. The findings offer practical insights for hospitality organizations to improve employees’ job attitudes and behaviors.